2014
DOI: 10.1016/j.neuroimage.2014.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Longer gestation is associated with more efficient brain networks in preadolescent children

Abstract: Neurodevelopmental benefits of increased gestation have not been fully characterized in terms of network organization. Since brain function can be understood as an integrated network of neural information from distributed brain regions, investigation of the effects of gestational length on network properties is a critical goal of human developmental neuroscience. Using diffusion tensor imaging and fiber tractography, we investigated the effects of gestational length on the small-world attributes and rich club … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 76 publications
(111 reference statements)
6
58
0
Order By: Relevance
“…The biological underpinning for an elevated risk of poor development is multifactorial and related to the curtailment of brain development, resulting in reduced gray matter volume, underdevelopment of neural and physiologic pathways critical to supporting brain growth postnatally, and subsequent learning difficulties arising from behavioral disorders. 1,2 Although early birth may be indicated and of demonstrated short-term benefit for selected highrisk pregnancies (eg, hypertension, prolonged pregnancy, suspected fetal growth restriction, prelabor rupture of membranes at term), for many conditions evidence is lacking or suggests little benefit (eg, suspected fetal macrosomia, maternal diabetes, preterm prelabor rupture of membranes). 33 -39 Furthermore, clinical research suggests that the threshold for planned birth and the gestational age for intervening has decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological underpinning for an elevated risk of poor development is multifactorial and related to the curtailment of brain development, resulting in reduced gray matter volume, underdevelopment of neural and physiologic pathways critical to supporting brain growth postnatally, and subsequent learning difficulties arising from behavioral disorders. 1,2 Although early birth may be indicated and of demonstrated short-term benefit for selected highrisk pregnancies (eg, hypertension, prolonged pregnancy, suspected fetal growth restriction, prelabor rupture of membranes at term), for many conditions evidence is lacking or suggests little benefit (eg, suspected fetal macrosomia, maternal diabetes, preterm prelabor rupture of membranes). 33 -39 Furthermore, clinical research suggests that the threshold for planned birth and the gestational age for intervening has decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal brain development accelerates rapidly in the later stages of pregnancy from 32 weeks' gestation, making it vulnerable to disruption from shortened gestation. 1,2 There is growing evidence that, in addition to preterm birth (≤37 weeks' gestation), infants born early term (37-38 weeks) have a greater risk of neurodevelopmental impairment or poor school performance compared with infants born at the optimal time. 3 -7 Early childhood development is also important for future educational achievement, health, and well-being, 8 with 11% to 17% of children aged 4 to 6 years considered to be developmentally high risk (DHR) by school age.…”
mentioning
confidence: 99%
“…A recent cross-sectional study reported a significant positive association between length of gestation and increased local network efficiency, particularly in bilateral superior parietal cortex (and precuneus) (Kim et al, 2014), which was interpreted by the authors as underlying the impact of length of gestation on structural hubs that are critical for global neural communication and integration (Collin et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…These difficulties persist through adolescence and young adulthood and may be exacerbated by disorders of executive function and attention. Over the past decade, multiple magnetic resonance imaging (MRI) studies of brain connectivity suggest that these difficulties of the prematurely born are related to alterations in functional and structural networks (Kim et al 2014; Constable et al 2012; White et al 2014; Salvan et al 2013). Similarly, PT neonates show disruptions in connectivity (Smyser et al 2010; Doria et al 2010), suggesting that PT birth results in both proximate and long-lasting changes in functional organization of the developing brain.…”
Section: Introductionmentioning
confidence: 99%